2020
DOI: 10.1038/s41467-019-14233-8
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenically-driven increases in the risks of summertime compound hot extremes

Abstract: Compared to individual hot days/nights, compound hot extremes that combine daytime and nighttime heat are more impactful. However, past and future changes in compound hot extremes as well as their underlying drivers and societal impacts remain poorly understood. Here we show that during 1960-2012, significant increases in Northern Hemisphere average frequency (~1.03 days decade −1 ) and intensity (~0.28°C decade −1 ) of summertime compound hot extremes arise primarily from summer-mean warming. The forcing of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
138
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(143 citation statements)
references
References 65 publications
4
138
1
Order By: Relevance
“…However, there exists a negative trend in the number of heat event days in southern North China, where the downtrend is possibly reflected as a regional response to inter-decadal and inter-annual variability 35 , 36 . Also, some other studies suggested that such a unique regional changing feature under global warming is possibly attributed to changes in aerosol, and regional land use and management 1 .…”
Section: Changes In Compound Drought and Heat Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there exists a negative trend in the number of heat event days in southern North China, where the downtrend is possibly reflected as a regional response to inter-decadal and inter-annual variability 35 , 36 . Also, some other studies suggested that such a unique regional changing feature under global warming is possibly attributed to changes in aerosol, and regional land use and management 1 .…”
Section: Changes In Compound Drought and Heat Eventsmentioning
confidence: 99%
“…Extreme weather and climate events have been widely studied over the past decades 1 3 . Research on changes in extreme heat events and drought events has been conducted in different regions of the world 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of CMIP is to investigate and improve climate model diagnosis, intercomparison, data access, etc. Extensive research to evaluate model simulations of extreme temperature started with the release of phase 5 of CMIP (CMIP5) models (Guo et al 2013;Sillmann et al 2013aSillmann et al , 2013bZhou et al 2014;Wang et al 2020). Chen and Sun (2015) revealed that for some extreme temperature indices, the model spread in CMIP5 is reduced compared with CMIP3.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the co‐variance of atmospheric variables, such as geopotential height and specific humidity with hot extremes as in‐tandem systematic responses to anthropogenic warming (IPCC AR5) obscures the causal relationship between these factors. Here, detrending of both station‐level and regional‐mean series is achieved by removing the seasonal mean of T max / T min for each year from daily observations, while considering the dominance of seasonal mean warming in the frequency increase in the three types of hot extremes and its attribution to anthropogenic warming (Wang et al ., 2020). Adopting other linear detrending techniques did not alter event identification in a significant manner (results not shown).…”
Section: Methods and Definitionmentioning
confidence: 99%
“…With a general expectation of cooler nights, however, people tend to be less vigilant against nighttime hot extremes, further exacerbating health consequences caused by daytime heat, leading to a significant increase of reported nighttime fatality rates (Murage et al ., 2017). Given that an increasing prevalence of compound hot extremes in populous areas can be expected (Wang et al ., 2020), both the climate science and human health communities must pay more attention to this largely overlooked yet more dangerous type of hot extreme.…”
Section: Introductionmentioning
confidence: 99%